Investigation of mega-cusp formation causing coastal erosion in Viet nam - Nguyen, Xuan Tinh (2020)
Construction of coastal structures or upstream hydroelectric dams will obviously cause erosion in coastal estuaries due to the lack of sediment supply. However, in coastal areas located far from the estuary, where there are often beautiful beaches, sometimes occurs severe coastal erosion caused by the formation of the mega-cusp. If the local beach resort is developed without understanding about this phenomenon, it will cause great economic losses. Tanaka et al., 2018 have been investigated the serious coastal erosion and huge damages to the beach resort infrastructure on My Khe Beach in Da Nang City of Vietnam based on the analysis of detected shoreline positions from the Google Earth images. He found that the formation of seasonal mega-cusp is one of the key causing the coastal disaster in this area. By using the spectrum analysis method on the detected shoreline positions, this study is found a strong correlation between the maximum power spectral which occurred as mega-cusp formation and strong wave conditions during the Northeast Monsoon season.